Compensation, Training and Development of Turnover Intention for Creative MSME Employees in Bandung City - Razka Gisnatiansyah; Ivan Gumilar Sambas Putra (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2022)
Every MSME always expects their employees to have good working performance because having such qualified employees may provide optimal contributions for the organization. Besides, by having employees with good working performance, MSMEs can improve their business performance. The purpose of this research is to identify the influence of compensation, training, and development on the employee turnover intention. Using simple random sampling, questionnaires are distributed to employees of creative industries of MSMEs in Bandung. The method used for data analysis is descriptive-verificative method with multiple regression model. The data processing is conducted by using the SPSS software version 27 for windows. The results of the research indicate that compensation has significant influence on the employee turnover intention, and so do the training and development. The two variables are able to provide contributions to the employee turnover intention of 77,3%, while the rest is influenced by the variables which are not investigated in this research.